Informal-formal workers' transition in Nigeria: A livelihood analysis - Abiodun Oluwole Folawewo; Olusegun A. Orija (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This study evaluates the effects of the informal sector on Nigerian workers' livelihoods and analyses workers' transitions within the informal sector and between informal and formal employment. A binary logit model is applied to General Household Survey panel data for the periods 2010/11, 2012/13, and 2015/16. We find that informal employment has the greatest impact on workers' livelihoods in terms of earnings. Results also indicate the existence of a high level of dynamic transition of workers within different types of informal employment. Our results further indicate that both self-employed and wage employed informal workers are likely to transit to formal employment, the likelihood being higher for the upper-tier informal wage employed. While informally employed workers have a very high chance of transiting to formal employment, formal workers have a much lower chance of transiting to informal employment. The policy implication of our results is the need to create better working conditions for informal workers.
Keywords: E26; J43; J46; 330; binary logistic regression; employment; formal; informal; Nigeria; transition